Condition of Islamic Education in Kokoda at Maebo Tribe Village, Village Klabinain, Aimas District, Sorong - Sukman S (JETL (Journal of Education, Teaching and Learning), 2018)
This study was conducted to investigate the implementation process of Islamic religious education in the public sphere Kokoda. Especially those living in Maebo Village, Sorong, West Papua. Further study is intended to look at the obstacles faced by educators in performing their duties in Maebo Village. This research was conducted with qualitative methods by interviewing objects associated with the process in the field. Based on the facts obtained, this study reveals several things, such as: first, from existing educational facilities, in new Maebo village has a primary school run by a private foundation. Only state schools still require education personnel can continue to carry out the activities of the school. Second, the constraints faced by the people in the village of Kokoda Maebo in studying is their own consciousness. The majority of children are still more concerned with work than school. This is attempted to be addressed by teachers in order that future generations Kokoda existing communities can the better quality of life.